SYMBOLIC ANNIHILATION TERHADAP EKSISTENSI PEREMPUAN DALAM SERIAL BRIDGERTON (2020) - Putri, Rizqi Auliawati; Saktiningrum, Nur (Sunan Kalijaga State Islamic University Yogyakarta, 2021)
This research examines the discrimination traits experienced by three female characters in the Bridgerton series. This research uses the symbolic annihilation concept by Gaye Tuchman and the theory of existentialist feminism by Simone de Beauvoir to describe the discriminatory traits experienced by the three female characters and reveal their resistance efforts to respond to the discrimination. This research uses qualitative descriptive methods to elaborate the findings and the theories. This research finds that women's existence in this series is presented as the party who gets trivialization, omission, and condemnation. Despite being subjected to annihilation traits, the three female characters in this series do not remain silent and accept what has been set by their family and society. Thus, these three female characters take the resistance by staying true to themselves and standing firm in their convictions. The symbolic annihilation they experienced then used as a reference to prove herself that as a woman they can still exist even though being discriminated against by society.